Editorial for Special Issue: Recent Advances in Space Debris - Lorenzo Olivieri; Kanjuro Makihara; Leonardo Barilaro (Applied Sciences, 2024)
The near-Earth space debris environment represents an existing hazard for human activities in space [...]